Late Qing parliamentarism and the borderlands of the Qing Empire—Mongolia, Tibet, and Xinjiang (1906–1911) - Moniz Bandeira, Egas (Journal of Eurasian Studies, 2020)
The article examines the relationship between the late Qing constitutional movement of 1905–1911 and the vast borderland regions of the Qing Empire–that is, Mongolia, Tibet, and Xinjiang. It traces how intellectuals and officials concerned with devising constitutional policies foresaw the integration of these regions into the nascent parliamentary institutions at the provincial and central levels. The article argues that the status of the borderlands played a significant role in late Qing constitutional debates, and that debates on borderland constitutionalism were a phenomenon of a wider constitutional wave affecting Eurasia in the 1900s. Chinese intellectuals and officials felt the competition of the emerging parliamentary institutions in Russia and the Ottoman Empire, and anticipating that constitutional and parliamentarist movements among Mongols, Tibetans, and Turki could lead to the separation of the respective regions, they hoped that parliamentary representation, albeit limited, would be an instrument against centrifugal tendencies on the borders. Hence, they called for constitutional reforms in China and for the inclusion of the borderland populations into the new parliamentary institutions. Yet, arguing with the sparse population of the borderlands as well as with their alleged economic and cultural backwardness, they denied the direct application of the constitutional plan to these territories. The differentiated policies eventually applied to the borderlands were a lackluster compromise between these conflicting interests.
Keywords: Constitutional history of China; history of Mongolia; history of Xinjiang; imperialism; Late Qing History; parliamentarism in China; Political Consultative Council (Zizhengyuan)